The Role Of The Internal Poetic Rhythem Highlighting The Poetic Meaning Of The (Malaye Jazeeri) Poetry (Mn D dl Kovana Hazam) As Model - KHORSHEED ABDULLAH, HALEEMA (Journal of Duhok University, 2019)
This paper entitled (The Role of Implicit Poetic Rhythm in Highlighting the Meaning of the Poetry) has been selected to explain the importance of implicit poetic rhythm and also to reveal the thought and poetic meaning. It is also aimed at showing the poet’s coordination abilities in poetic rhythm, specially implicit rhythm and poetry meaning. Since the internal rhythm has been known as implicit rhythm covering a wide range of settings such as the phonetic, syllabus, word, and sentence. This paper is made up of an introduction and two sections, the first section dealt with the rhythm, poetic rhythm, and types of rhythm. The second section discussed the practical aspect of the role of the internal poetic rhythm in highlighting the poetic meaning of the (Malye Jazeeri) poetry (Mn D Dl Kovan Hazarn) as a sample. Accordingly, this paper based on theoretical analysis. It is worth-mentioning that the results and the references have been pointed out.